2009
DOI: 10.1016/j.hrtlng.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Information from health care professionals about sexual function and coexistence after myocardial infarction: A Swedish national survey

Abstract: OBJECTVE: After a myocardial infarction (MI) many patients and their partners experience problems with marital and sexual life.METHODS: A Swedish national survey was carried out to obtain knowledge on the information provided by cardiac healthcare professionals on the subject of sexual function and coexistence after an MI. It consisted of a questionnaire that was designed, tested and sent to 121 coronary care units (CCUs). RESULTS:The results revealed that the CCU teams rarely provided oral or written informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 20 publications
6
60
0
4
Order By: Relevance
“…10 Furthermore, a US study on nurses working with patients after a myocardial infarction and national surveys in Ireland and Sweden in cardiac rehabilitation centers and coronary care unit teams have shown comparable findings. 11,14,16 It can be concluded that not discussing sexual health and providing sexual counseling in different cardiac settings is a general problem that does not only relates to HF nurses, but also other cardiac healthcare providers. This limited implementation of sexual counseling in practice may rightfully be called a concern, because a considerable number of HF patients experience sexual difficulties which have a negative effect on their own quality of life and that of their partners.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, a US study on nurses working with patients after a myocardial infarction and national surveys in Ireland and Sweden in cardiac rehabilitation centers and coronary care unit teams have shown comparable findings. 11,14,16 It can be concluded that not discussing sexual health and providing sexual counseling in different cardiac settings is a general problem that does not only relates to HF nurses, but also other cardiac healthcare providers. This limited implementation of sexual counseling in practice may rightfully be called a concern, because a considerable number of HF patients experience sexual difficulties which have a negative effect on their own quality of life and that of their partners.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ivarsson et al [39] showed that Swedish patients do not receive adequate information and support from the healthcare professionals about sexuality in relation to heart disease. It is common for healthcare professionals to feel uncomfortable to starting a dialogue about sexuality.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Health personnel do not currently address sexual issues on a regular basis with post MI patients, especially not with spouses [9]. One reason can be that nurses are unsure about how to deal with questions and feel that they do not have enough knowledge about the subject [10].…”
Section: Introductionmentioning
confidence: 99%